Towards the consolidation of a plural and sustainable model for the control of foreign investments and their impact on the european market (Justicia &Derecho, 2025)
Since 2017, the European Union has substantially modified its position on certain foreign investments originating from specific countries or intended for particular strategic economic sectors. This article analyses the complex, multifaceted European model designed to control foreign investment in strategic sectors. It emphasises a model based on the need to guarantee national security, promote reciprocity, and minimise unfair practices, which form the basis for accepting foreign investment flows. Assuming its constant evolution, the model is based on the following principles. The article concludes with an analysis of existing regulatory proposals to consolidate a sustainable approach.
Keywords: foreign investments; national security; european plural model; regulatory framework; strategic sustainability